Preparation method and application of special-shaped double-shell hollow nanomaterial

By using low-temperature and low-speed centrifugation, freeze-drying and procedural carbonization in high-temperature alkaline environments, a heterotyped bi-shell hollow nanomaterial with metal oxides and inner shells is prepared, which solves the problem of poor stability of existing MOFs materials in high-temperature alkaline environments, and achieves high catalytic activity and recyclability effects.

CN118185045BActive Publication Date: 2025-03-18ZHEJIANG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410428818.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-10
Publication Date
2025-03-18
Estimated Expiration
2044-04-10

AI Technical Summary

Technical Problem

Existing metal-organic framework (MOFs) materials have poor stability in high-temperature alkaline environments, making it difficult to achieve high catalytic activity and recyclability.

Method used

Using low-temperature and low-speed centrifugation, freeze-drying and procedural heating carbonization, a heteroformed bi-shell hollow nanomaterial with metal oxides and carbon in the outer shell layer was prepared by using MOFs as a sacrificial template.

Benefits of technology

The stability of the material in a high-temperature alkaline environment is significantly improved, and a heterotype bicanal hollow nanomaterial with high catalytic activity and recyclability can be prepared without multiple steps of modification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118185045B_ABST
    Figure CN118185045B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method and application of a heterogeneous double-shell hollow nanomaterial. The main purpose is to prepare a heterogeneous double-shell catalyst material using MOFs as a precursor, ensure synchronous crystallization of the inner and outer surfaces of the double-shell material by low-temperature centrifugation, then put the material into a freeze dryer for freeze drying to ensure the integrity of the carbon skeleton, and finally prepare a heterogeneous double-shell hollow nanomaterial with carbon as an inner shell and metal oxide as an outer shell by high-temperature pyrolysis. The Zr / C heterogeneous double-shell hollow nanomaterial of the present invention has a simple preparation process and high crystallinity. The heterogeneous double-shell hollow nanomaterial uses MOFs of different metal ions as sacrificial templates, and the catalytically active metal sites can be evenly dispersed. The outer shell is a metal oxide layer with highly consistent exposed crystal faces, and the inner shell is a spherical carbon layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of micro-nano material preparation, and in particular to a preparation method and application of a special-shaped double-shell hollow nano material. Background Art

[0002] Metal-organic frameworks (MOFs) are solid materials with permanent porosity. They form a three-dimensional coordination network structure through the coordination of nodes (metal ions or clusters) and organic bridges. The metal ions and organic ligands are diverse, and their structures have a certain periodicity. Therefore, their structures are predictable during the design and synthesis process. In addition, the size of the organic ligands can be adjusted to give them a larger specific surface area and pore size. However, most MOFs still have stability issues, especially under harsh reaction conditions with elevated temperatures in alkaline environments, making it difficult to achieve high catalytic activity and recyclability. MOFs-derived materials generally have a higher tolerance to harsh reaction conditions.

[0003] Zirconium-based MOFs materials have become a MOFs-derived precursor material that has attracted much attention from researchers due to their excellent physical and chemical stability. In the modification process of zirconium-based MOFs, other catalyst materials that can form good effects with metal catalytic sites are added, such as U66SA synthesized by Vitsarut.T et al. (Small 2021, 17, 2170108). By doping the required amount of Al into the uniform porous structure of zirconium-based MOFs, the metal catalytic sites can form a catalyst with good effects with them. 3+ Catalytic sites can significantly optimize the acid strength and acid site density in MOFs-based catalysts to improve catalytic efficiency. Z. Lu et al. successfully synthesized a new isomer of NU-1000 by deliberately adjusting the typical zirconium-based MOFs (ZR-MOA) joints (J. Am. Chem. Soc., 2023, 145, 4150-4157). V. Guillerm et al. prepared a series of new hydrophobic isoreticular porous zirconia-based MOFs (Angew. Chem. Int. Ed., 51, 9267-9271), which have a rare combination of one-dimensional pore system, Lewis acidity and hydrophobic properties. These adjustments give them excellent water stability and cycle stability. Jianan Zhang et al. synthesized a double shell structure (ACS Nano, 2015, 9, 3, 3369–3376), which provides a double shell of Fe3C and carbon to limit the dissolution of Fe3O4, thereby greatly improving the cycle life of Fe3O4 and enhancing the activity of the material. Double-shell materials have excellent application prospects, and the special-shaped double-shell hollow nanomaterials not only retain the original characteristics of the double shell, but also have two exposed crystal surface structures inside and outside, which are more valuable for research.

[0004] Here, we propose a method for preparing a heterogeneous double-shell hollow nanomaterial, using MOFs as sacrificial templates, and synthesizing a heterogeneous double-shell hollow nanomaterial with an outer shell of metal oxide and an inner shell of carbon by low-temperature and low-speed centrifugation, freeze drying, programmed temperature carbonization, etc. The heterogeneous double-shell hollow nanomaterial proposed in the present invention has a simple preparation process, and the obtained material has the advantages of rich acid sites, highly consistent exposed crystal faces, fast mass transfer rate, excellent electrical properties, active surface electrons and high conductivity. Summary of the invention

[0005] The present invention provides a preparation method and application of a heterogeneous double-shell hollow nanomaterial. The main purpose is to prepare a heterogeneous double-shell catalyst material using MOFs as a precursor, ensure synchronous crystallization of the inner and outer surfaces of the double-shell material by low-temperature centrifugation, then put the material into a freeze dryer for freeze drying to ensure the integrity of the carbon skeleton, and finally prepare a heterogeneous double-shell hollow nanomaterial with carbon as the inner shell and metal oxide as the outer shell by high-temperature pyrolysis.

[0006] According to the embodiment provided by the present invention, a method for preparing a special-shaped double-shell hollow nanomaterial is provided.

[0007] A method for preparing a special-shaped double-shell hollow nanomaterial, the method comprising the following steps:

[0008] S1. dissolving a metal salt and a phthalic acid-based organic compound in a reaction solvent to obtain a mixed solution;

[0009] S2. Adding acetic acid to the mixed solution, and then mixing evenly to obtain a reaction solution;

[0010] S3. The reaction solution was transferred to a reactor, sealed and placed in a heater to heat the reaction. After the reaction was completed, the product was centrifuged at a low temperature of 4 to 9 ° C and a low speed of 500-2000 RPM, washed and freeze-dried to obtain a product;

[0011] S4. The product obtained in step S3 is placed in a tubular furnace, air is introduced first, the temperature is raised to 200-350°C, and the temperature is kept for 0.5-1h, and then nitrogen is introduced, the temperature is raised to 500-800°C, and the temperature is kept for 2-6h to obtain a special-shaped double-shell hollow nanomaterial.

[0012] Preferably, in step S1, the metal salt is one or more of zirconium tetrachloride, cobalt nitrate, sodium molybdate, ferric chloride, etc. The phthalic acid organic compound is terephthalic acid, and the molar ratio of the metal salt to terephthalic acid (H2BDC) is 1:0.8 to 1:1.2.

[0013] Preferably, in step S2, the mixed solution is stirred at room temperature for 30 minutes. The time should not be too long, and it needs to be left to stand for 30 to 50 minutes after the stirring is completed.

[0014] Preferably, in step S3, the heater is slowly heated to 100-130°C and maintained for 12-36 hours, the centrifugal temperature is 4-9°C, and the centrifugal speed is 500-2000RPM to ensure synchronous crystallization of the inner and outer surfaces of the double shell material.

[0015] Preferably, in step S3, the freeze-drying temperature is set to -50°C to -60°C, and the time is 12 to 24 hours.

[0016] Preferably, in step S3, the product is washed three times with methanol and DMF alternately, and then washed 4 to 6 times with methanol in a Soxhlet extractor.

[0017] Preferably, in step S4, the tubular furnace is heated in stages. When the temperature in the first stage is raised to 200-350°C, air is introduced and maintained for 2-4 hours, so that the outer layer of crystal can remain intact and protected from subsequent high temperature damage; the second stage is heated from 350°C to 500-800°C and maintained for 2-4 hours. At this time, nitrogen is introduced into the tubular furnace and maintained for 3 hours, which can cause the central structure to shrink outward to form an internal spherical cavity.

[0018] The beneficial effect of the present invention is that a heteromorphic double-shell hollow nanomaterial is prepared simply and efficiently, which can significantly improve the stability of the metal organic framework in a high temperature alkaline environment. Without the need for multi-step modification, a heteromorphic double-shell hollow nanomaterial with an outer shell of metal oxide and an inner shell of carbon can be prepared.

[0019] Compared with the prior art, the present invention has the following advantages:

[0020] (1) The novel heteromorphic double-shell hollow nanomaterial has a simple preparation process and high crystallinity; the heteromorphic double-shell hollow nanomaterial uses MOFs of different metal ions as sacrificial templates, the catalytic active metal sites can be evenly dispersed, the outer shell is a metal oxide layer with a highly uniform exposed crystal surface, and the inner shell is a spherical carbon layer.

[0021] (2) Compared with other double-shell materials, this special-shaped double-shell hollow nanomaterial has a higher tolerance to high-temperature alkaline conditions, which can ensure recyclability, and low temperature and low rotation speed can ensure synchronous crystallization inside and outside, and the structure of the material is more stable. The exposed crystal surface of the outer shell is highly consistent, and the rich acid sites ensure high catalytic activity and selectivity. The inner carbon layer ensures strong electron transfer ability and high conductivity, and the electrical properties are excellent.

[0022] (3) The freeze-dried product of the novel metal / carbon heterogeneous double-shell hollow nanomaterial of the present invention protects its crystalline morphology, and the huge spherical cavity inside can improve the mass transfer rate of the material.

[0023] In summary, the heteromorphic double-shell hollow nanomaterial described in the present application has a simple preparation process, rich acid sites, highly consistent exposed crystal faces, fast mass transfer rate, excellent electrical properties, active surface electrons and high electrical conductivity, and has potential application prospects in electrocatalysis and photocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 TEM image of the special-shaped double-shell hollow nanomaterial prepared by the present invention.

[0025] Figure 2 TEM images of the heteromorphic double-shell hollow nanomaterial in Example 1 and the non-hollow nanomaterial in Comparative Example 1.

[0026] Figure 3 This is the XPS graph of the heterogeneous double-shell hollow nanomaterial in Example 1.

[0027] Figure 4 This is the NH3-TPD spectrum of the heterogeneous double-shell hollow nanomaterial in Example 1.

[0028] Figure 5 This is the electrochemical impedance Nyquist diagram comparing the heterogeneous double-shell hollow nanomaterial in Example 1 with ordinary ZrO2.

[0029] Figure 6 The electrostatic potential and work function diagram of the heterogeneous double-shell hollow nanomaterial in Example 1 compared with ordinary ZrO2.

[0030] Figure 7 It is the desorption rate of the TETA-DEEA solution in Examples 2 and 3 after adding the heteromorphic double-shell hollow nanomaterial in Example 1.

[0031] Figure 8 It is the desorption rate of the MEA solution in Examples 4 and 5 after adding the heteromorphic double-shell hollow nanomaterial in Example 1.

[0032] Fig. 9 The relative heat load comparison diagram of TETA-DEEA solution and MEA solution in Examples 2, 3, 4 and 5 is shown. DETAILED DESCRIPTION

[0033] The present invention is further described by the following specific examples, but the protection scope of the present invention is not limited to the following examples.

[0034] Example 1

[0035] A method for preparing a special-shaped double-shell hollow nanomaterial, the method comprising the following steps:

[0036] (1) Preparation of zirconium-based metal organic framework: Take 1.07g of zirconium tetrachloride (ZrCl4) and 0.79g of terephthalic acid (H2BDC), dissolve the zirconium salt and terephthalic acid organic matter in methanol solvent, add 10ml of acetic acid, and then stir for 30min. After stirring, let it stand for 30-50min to mix evenly. Place the above mixture in an autoclave, react at 100°C for 36 hours, wash with methanol and DMF alternately, centrifuge at low temperature and low speed, where the centrifuge temperature is 5°C and the speed is 1000RPM, and separate the zirconium-based metal organic framework MOF.

[0037] (2) Freeze-drying the material: Place the zirconium-based metal organic framework obtained in step (1) into a freeze dryer, set the temperature to -60°C, and freeze for 12 hours.

[0038] (3) Preparation of heterogeneous double-shell hollow nanomaterials: The material obtained in step (2) was placed in a tubular furnace, and air was first introduced at a rate of 150 mL / min, the temperature was raised to 350°C, and the temperature was kept for 1 h. Subsequently, nitrogen was introduced at a rate of 150 mL / min, the temperature was raised to 700°C, and the temperature was kept for 3 h to obtain Zr / C heterogeneous double-shell hollow nanomaterials.

[0039] Comparative Example 1

[0040] A method for preparing a non-hollow nanomaterial, the method comprising the following steps:

[0041] (1) Preparation of zirconium-based metal organic framework: Take 1.07g of zirconium tetrachloride (ZrCl4) and 0.79g of terephthalic acid (H2BDC), dissolve the zirconium salt and terephthalic acid organic matter in methanol solvent respectively, add 10ml of acetic acid, and then mix well. Place the above mixture in an autoclave, react at 100°C for 36 hours, wash with methanol and DMF alternately, centrifuge at low temperature and low speed, wherein the centrifuge temperature is 5°C and the speed is 1000RPM, and separate the zirconium-based metal organic framework MOF.

[0042] (2) Freeze-drying the material: Place the zirconium-based metal organic framework obtained in step (1) into a freeze dryer, set the temperature to -60°C, and freeze for 12 hours.

[0043] (3) Preparation of heterogeneous double-shell hollow nanomaterials: The material obtained in step (2) was placed in a tubular furnace, air was introduced first, the temperature was raised to 350°C, and the temperature was kept for 1 hour, and then nitrogen was introduced, the temperature was raised to 500°C, and the temperature was kept for 3 hours to obtain a non-hollow nanomaterial.

[0044] Example 2

[0045] An application example of a special-shaped double-shell hollow nanomaterial, the application comprising the following steps:

[0046] (1) introducing CO2 into an organic amine aqueous solution containing TETA-DEEA, wherein the molar ratio of TETA to DEEA is 0.3 to 2:3, preferably 1:3, and the total amine concentration of the organic amine aqueous solution is 3 to 6 mol / L, preferably 4 mol / L;

[0047] (2) After the CO2 absorption is completed in step (1), the upper and lower liquid phases are separated and the CO2-enriched phase, i.e., the lower phase of the solution, is collected;

[0048] (3) The Zr / C heteromorphic double-shell hollow nanomaterial described in Example 1 is added to the CO2-rich phase. The amount of the Zr / C heteromorphic double-shell hollow nanomaterial added to the organic amine aqueous solution is 0.5-3 mg / mL, preferably 1 mg / mL. When 25% of the CO2 loading amount of the solution is desorbed at 90-98°C, the reaction energy consumption is calculated to achieve the regeneration of the organic amine under low energy consumption. The specific material properties and energy consumption reduction are as follows: Figure 7 and Fig. 9 As shown in the figure, it can be seen that when the heterogeneous double-shell hollow nanomaterials are added as catalysts, the reaction rate increases from 28mmol·min-1·L -1 Increased to 60mmol·min-1·L -1 , the reaction energy consumption was reduced by 56.44%.

[0049] Example 3

[0050] An application example of a special-shaped double-shell hollow nanomaterial, the application comprising the following steps:

[0051] (1) introducing CO2 into an organic amine aqueous solution containing TETA-DEEA, wherein the molar ratio of TETA to DEEA is 0.3 to 2:3, preferably 1:3, and the total amine concentration of the organic amine aqueous solution is 3 to 6 mol / L, preferably 4 mol / L;

[0052] (2) After the CO2 absorption is completed in step (1), the upper and lower liquid phases are separated, and the CO2-enriched phase, i.e., the lower phase of the solution, is collected, and the absorption amount of CO2 in the organic amine aqueous solution is greater than or equal to 0.75 molCO2 / mol amine solution;

[0053] (3) The Zr / C heteromorphic double-shell hollow nanomaterial described in Example 1 is added to the CO2-rich phase. The amount of the Zr / C heteromorphic double-shell hollow nanomaterial added to the organic amine aqueous solution is 0.5-3 mg / mL, preferably 1 mg / mL. When 30% of the CO2 loading amount of the solution is desorbed at 90-98°C, the reaction energy consumption is calculated to achieve the regeneration of the organic amine under low energy consumption. The specific material properties and energy consumption reduction are as follows: Figure 7 and Fig. 9As shown in the figure, it can be seen that when the heterogeneous double-shell hollow nanomaterials are added as catalysts, the reaction rate increases from 28mmol·min-1·L -1 Increased to 60mmol·min-1·L -1 , the reaction energy consumption was reduced by 57.3%.

[0054] Example 4

[0055] An application example of a special-shaped double-shell hollow nanomaterial, the application comprising the following steps:

[0056] (1) introducing CO2 into an organic amine aqueous solution containing MEA, wherein the concentration of the organic amine aqueous solution is 2 to 10 mol / L, preferably 5 mol / L;

[0057] (2) After the CO2 absorption in step (1) is completed, the CO2 content in the organic amine aqueous solution is 0.1 to 1.0 mol CO2 / mol organic amine, preferably 0.5 to 0.53 mol CO2 / mol organic amine;

[0058] (3) The Zr / C heteromorphic double-shell hollow nanomaterial described in Example 1 is added to the solution that has been absorbed. The amount of the Zr / C heteromorphic double-shell hollow nanomaterial added to the organic amine aqueous solution is 0.5-3 mg / mL, preferably 1 mg / mL. When 25% of the CO2 amount loaded in the solution is desorbed at 90-98° C., the reaction energy consumption is calculated to achieve the regeneration of the organic amine under low energy consumption. The specific material properties and energy consumption reduction are as follows: Figure 8 and Fig. 9 As shown in the figure, it can be seen that when the heterogeneous double-shell hollow nanomaterials are added as catalysts, the reaction rate increases from 24mmol·min-1·L -1 Increased to 55mmol·min-1·L -1 , reaction energy consumption is reduced by 60%.

[0059] Example 5

[0060] An application example of a special-shaped double-shell hollow nanomaterial, the application comprising the following steps:

[0061] (1) introducing CO2 into an organic amine aqueous solution containing MEA, wherein the concentration of the organic amine aqueous solution is 2 to 10 mol / L, preferably 5 mol / L;

[0062] (2) After the CO2 absorption in step (1) is completed, the CO2 content in the organic amine aqueous solution is 0.1 to 1.0 mol CO2 / mol organic amine, preferably 0.5 to 0.53 mol CO2 / mol organic amine;

[0063] (3) The Zr / C heteromorphic double-shell hollow nanomaterial described in Example 1 is added to the absorbed solution. The amount of the Zr / C heteromorphic double-shell hollow nanomaterial added to the organic amine aqueous solution is 0.5-3 mg / mL, preferably 1 mg / mL. When 30% of the CO2 amount of the solution load is desorbed at 90-98° C., the reaction energy consumption is calculated to achieve the regeneration of the organic amine under low energy consumption. The specific material properties and energy consumption reduction are as follows: Figure 8 and Fig. 9 As shown in the figure, it can be seen that when the heterogeneous double-shell hollow nanomaterials are added as catalysts, the reaction rate increases from 24mmol·min-1·L -1 Increased to 55mmol·min-1·L -1 , the reaction energy consumption was reduced by 69.99%.

Claims

1. Application of heterogeneous double-shell hollow nanomaterials as catalysts in desorption of CO2, characterized in that: The method for preparing the heteromorphic double-shell hollow nanomaterial comprises the following steps: S1. dissolving a metal salt and a phthalic acid-based organic compound in a reaction solvent to obtain a mixed solution; The metal salt is one or more of zirconium tetrachloride, cobalt nitrate, sodium molybdate, and ferric chloride; The phthalic acid organic substance is terephthalic acid; The molar ratio of the metal salt to terephthalic acid is 1:0.8 to 1:1.2; S2. Adding acetic acid to the mixed solution, and then mixing evenly to obtain a reaction solution; S3. The reaction solution is transferred to a reactor, sealed and placed in a heater to raise the temperature to 100-130°C and maintained for 12-36 hours. After the reaction is completed, the reaction solution is centrifuged at 4-9°C and a low speed of 500-2000 RPM, washed and freeze-dried. The freeze-drying temperature is set to -50°C to -60°C for 12-24 hours to obtain the product. S4. The product obtained in step S3 is placed in a tubular furnace, air is introduced first, the temperature is raised to 200-350°C, and the temperature is kept for 0.5-1h, and then nitrogen is introduced, the temperature is raised to 500-800°C, and the temperature is kept for 2-6h to obtain a special-shaped double-shell hollow nanomaterial.

2. The use according to claim 1, characterized in that: In step S1, the reaction solvent is methanol.

3. The use according to claim 1, characterized in that: In step S2, the conditions for uniform mixing are: stirring for 20 to 40 minutes, and standing for 30 to 50 minutes after stirring.

4. The use according to claim 1, characterized in that: In step S3, washing includes: washing the product multiple times with methanol and N,N-dimethylformamide alternately, and then washing the product multiple times with methanol in a Soxhlet extractor.

5. The use according to claim 1, characterized in that: In step S4, the rate of introducing air is 100-200 mL / min; The rate of nitrogen introduction is 100~200mL / min.

Citation Information

Patent Citations

  • Manganese-doped Li<2>FeSiO<4> / graphene hollow nanosphere cathode material and preparation method thereof

    CN107394125A

  • UIO-66 derived carbon material catalyst, preparation method thereof and application of UIO-66 derived carbon material catalyst in catalysis of carbon dioxide desorption

    CN115869932A